Association between atherogenic index of plasma and periodontitis among U.S. adults - Jing Sun; Ge Guo (BMC Oral Health, 2023)
Abstract Background Serum lipids have been proven to influence periodontitis. The atherogenic index of plasma (AIP) is an important marker of lipid levels. The purpose of this study was to investigate the association between periodontitis and AIP in adults. Methods The study included participants from the 2009–2014 National Health and Nutrition Examination Survey who received a complete periodontal exam and a complete record of AIP. AIP was calculated as log10 (triglycerides/high-density lipoprotein cholesterol). Periodontitis can be classified into four categories based on attachment loss and probing depth (no periodontitis, moderate periodontitis, mild periodontitis, and severe periodontitis). Multivariable logistic regression after adjusting and hierarchical analysis were conducted to investigate the relationship between periodontitis and AIP in adults. Results The final sample included 4,371 participants, representing approximately 60 million people in the United States. Periodontitis among the AIP groups (quartile, Q1-Q4) was statistically significant (P < 0.05). Univariate analysis showed that AIP was associated with the incidence of periodontitis (P < 0.05), but not with the severity of periodontitis (P > 0.05) in participants. Multifactorial logistic regression analysis showed no correlation between the incidence of periodontitis and AIP among all participants (the trend P-value = 0.341), but a significant association with AIP in the non-smoking participants (the trend P-value = 0.031). Conclusion There was a significant correlation between periodontitis and AIP in the non-smoking population.